2012
DOI: 10.1016/j.neuroscience.2012.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The human vestibular cortex revealed by coordinate-based activation likelihood estimation meta-analysis

Abstract: Abstract-The vestibular system contributes to the control of posture and eye movements and is also involved in various cognitive functions including spatial navigation and memory. These functions are subtended by projections to a vestibular cortex, whose exact location in the human brain is still a matter of debate . The vestibular cortex can be defined as the network of all cortical areas receiving inputs from the vestibular system, including areas where vestibular signals influence the processing of other se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
384
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(425 citation statements)
references
References 129 publications
(215 reference statements)
34
384
1
6
Order By: Relevance
“…These preliminary results showed significant activation over the major areas involved with multimodal functions of the vestibular system (Bense et al, 2001) and are in agreement with previous galvanic vestibular stimulation studies with fMRI (Eickhoff et al, 2006a;Fink et al, 2003;Smith et al, 2012;Stephan et al, 2005). Also, the results showed here corroborate with a meta-analysis study that evaluate the statistical analysis of the localization of the human vestibular cortex in neuroimaging studies using caloric vestibular stimulation, galvanic vestibular stimulation and auditory stimulus (Lopez et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…These preliminary results showed significant activation over the major areas involved with multimodal functions of the vestibular system (Bense et al, 2001) and are in agreement with previous galvanic vestibular stimulation studies with fMRI (Eickhoff et al, 2006a;Fink et al, 2003;Smith et al, 2012;Stephan et al, 2005). Also, the results showed here corroborate with a meta-analysis study that evaluate the statistical analysis of the localization of the human vestibular cortex in neuroimaging studies using caloric vestibular stimulation, galvanic vestibular stimulation and auditory stimulus (Lopez et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…A vestibular contribution to self-location seems of relevance here because the sensations of elevation and floating reported by the participants of Ionta et al's study are close to vestibular illusions reported by patients with damage to the otolithic vestibular system and the central vestibular structures (Schilder, 1935). Several regions of the TPJ located around the posterior end of the Sylvian fissure, such as the angular, supramarginal and superior temporal gyrus, and the regions located in the depth of the Sylvian fissure, such as the parietal operculum, insula and the retroinsular cortex, are strongly involved in vestibular processing (Chen, DeAngelis, & Angelaki, 2010;Grüsser, Pause, & Schreiter, 1990;Lopez, Blanke, & Mast, 2012). Lesions or seizures in the TPJ may alter the experience of self-location, such as during what are often called out-of-body experiences.…”
Section: Neural Bases Of Whole-body Ownership and Self-locationmentioning
confidence: 55%
“…Despite the obvious importance of vestibular signals, the cortical organization of the vestibular system is not yet well established. Unlike other sensory systems, the number of vestibular cortical areas and the information they represent are still under debate (Dieterich and Brandt 2015;Guldin and Grüsser 1998;Kahane et al 2003;Lopez and Blanke 2011;Lopez et al 2012).…”
Section: In This Paper We Examine Vestibular and Visual Processing Atmentioning
confidence: 99%
“…For the definition of area PIVC, in addition to previous descriptions (e.g., Deutschländer et al 2002;Dieterich et al 2003;Eickhoff et al 2006;Lopez and Blanke 2011;Lopez et al 2012;zu Eulenburg et al 2012), results of a random-effects group analysis of the vestibular localizer were used (Fig. 3C).…”
Section: Imaging Data Analysismentioning
confidence: 99%